Diet quality in relation to healthy ageing: the Israeli Longitudinal Study on Aging (ILSA)—a study protocol. Issue 4 (20th April 2019) - Goshen, Abigail; Goldbourt, Uri; Shohat, Tamar; Shimony, Tal; Keinan-Boker, Lital; Gerber, Yariv
Abstract : Introduction: Population ageing is accelerating rapidly in Israel as well as worldwide, necessitating adaptation of the healthcare system and consideration of new approaches that serve the specific needs of older adults. In addition to cognitive function, frailty is one of the most challenging expressions of physical and mental ageing, a multidimensional syndrome of increased vulnerability. Several studies have shown that low intake of certain micronutrients and protein is associated with higher risk of frailty and cognitive impairment. However, whether global diet quality is involved in the aetiology of the latter outcomes is unclear. Methods and analysis: We are conducting, among older adult subjects who took part in 'Mabat Zahav' (Israeli National Health and Nutrition Survey of Older Adults) in 2005–2006 (T0, n=1852), an extensive follow-up interview (T1) that includes comprehensive geriatric assessment and evaluation of general health and quality of life. Diet quality is evaluated using the Healthy Eating Index (HEI) 2010, based on 24-hour diet recall measured at T0 and T1. Frailty is assessed using two different approaches: the phenotype framework and the accumulation of deficits model. Cognitive function is assessed by Mini-Mental State Examination (MMSE) and cognitive decline is assessed by the difference between repeated MMSE measurements. Different analytic methods will be applied to evaluate the role of diet quality in development of frailty and cognitive decline with inverse probability weighting used to minimise attrition bias. About 600 subjects are expected to be interviewed between May 2017 and December 2019. Ethics and dissemination: Ethical approval was obtained from the Helsinki Committee of Sheba Medical Center, Tel Hashomer, Israel and the Ethical Committee of Tel-Aviv University. All participants sign an informed consent form. The findings of the study will be published in peer-reviewed journals.